Aim and Goals for Bilingual-Bicultural Education Short-Term and Long-Term Aspects - Johannesson, Ingvar; Lund Univ. (Sweden). Dept. of Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
Due to increasing numbers of immigrants since 1960, especially Finnish children, Sweden began to establish instructional objectives and policies for immigrant children. Stated aims clearly stress that the primary aim in the teaching of immigrant children in Swedish schools is to promote bilingualism. While the short-term aim is to produce functional bilingualism (equal ability to speak and read both languages), the long-term aim is to equalize the learning opportunities for these children in the regular school system. V. P. John and V. M. Herner (1971) propose four models of bilingual education: informal, supplementary, transition, and two-way. The Swedish model is a transition model which uses the native language as a bridge to the national language. The mother tongue (Finnish) is developed to a relatively high degree during pre-school years and the first two years in the compulsory school; Swedish is given subordinate importance until grade 3 when training in the national language is necessary. The objective is to reach functional bilingualism by the end of grade 3. Development in the native language after age 10 is highly dependent upon the individual child and parental support. (EA)
Educational level discussed: Elementary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bilingual Education; Bilingualism; Educational Objectives; Elementary Education; Equal Education; Foreign Countries; Sweden; Reports, Descriptive